2021
DOI: 10.1200/po.21.00030
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Molecular Tumor Registry to Support the Adoption of Precision Oncology Within an Academic Medical Center: The Duke University Experience

Abstract: PURPOSE Comprehensive genomic profiling to inform targeted therapy selection is a central part of oncology care. However, the volume and complexity of alterations uncovered through genomic profiling make it difficult for oncologists to choose the most appropriate therapy for their patients. Here, we present a solution to this problem, The Molecular Registry of Tumors (MRT) and our Molecular Tumor Board (MTB). PATIENTS AND METHODS MRT is an internally developed system that aggregates and normalizes genomic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In fact, if clinical validity can receive internal validation, for example in the context of a clinical study under an innovative design, clinical utility validation should include clinical benefit and be cost-effectiveness. The published experiences of advanced cancer patients treated according to the MTB recommendation demonstrate that adherence to MTB leads improved outcomes compared to the patients treated according to the physician's choice (Kato et al, 2020;Green et al, 2021). Particularly, a critical result of the MTB implementation is the increased enrollment in clinical trials.…”
Section: Regulatory and Pharmaco-economic Aspectsmentioning
confidence: 99%
“…In fact, if clinical validity can receive internal validation, for example in the context of a clinical study under an innovative design, clinical utility validation should include clinical benefit and be cost-effectiveness. The published experiences of advanced cancer patients treated according to the MTB recommendation demonstrate that adherence to MTB leads improved outcomes compared to the patients treated according to the physician's choice (Kato et al, 2020;Green et al, 2021). Particularly, a critical result of the MTB implementation is the increased enrollment in clinical trials.…”
Section: Regulatory and Pharmaco-economic Aspectsmentioning
confidence: 99%
“…25 Turnaround times between sample collection to results are also likely to be shorter with liquid biopsies. 7,28,29 Analysis of ctDNA can have additional functional uses, such as monitoring cancer progression, therapeutic response (e.g., resistance development), and possibly detecting early indications of recurrence through subsequent testing or longitudinal analysis. 7,30 However, because liquid biopsies do not directly target the primary tumour, they generally have reduced sensitivity compared with tissues samples, and, in some circumstances (e.g., certain cancer types, early-stage tumours, or patient-related factors), there may be limited ctDNA shed by tumours, which makes detection challenging.…”
Section: Strengths and Limitations Of Tissue Versus Liquid Biopsymentioning
confidence: 99%
“…31 Evidence from primary studies and systematic reviews also indicated that although liquid-based tests can detect actionable mutations, tissue-based tests generally have higher sensitivity and detection capability. 26,29,[52][53][54][55] Tissue-based tests provide higher quality genetic signals if the tumour can be accessed appropriately.…”
Section: Detection Capability Of Cgpmentioning
confidence: 99%
See 2 more Smart Citations